Resusitasi Pengendalian Kerusakan Di Unit Perawatan Intensif - Dhanu Pitra Arianto; Nurita Dian Kestriani (Fakultas Kedokteran Universitas Kristen Indonesia, 2020)
Abstrak Resusitasi dengan pengendalian kerusakanmenggambarkan suatu pendekatan ke perawatan awal pada pasien dengan cedera berat. Tujuan pendekatan ini untuk menjaga pasien tetap stabil dengan menghindari intervensi dan kondisi yang berisiko kepada keadaan perburukan dengan mengendalikan trias kematian, yaitu hipotermia, koagulopati, dan asidosis. Merupakan hal yang penting bahwa konsep dan kepraktisan pendekatan ini dipahami oleh semua yang terlibat dalam manajemen awal pasien trauma. Pendekatan ini dimulai dengan pemberian produk darah sejak awal, penghentian perdarahan dan pengembalian volume darah yang bertujuan untuk mengembalikan stabilitas fisiologis dengan cepat. Resusitasi dengan pengendalian kerusakan memilikibeberapa tambahan pendekatan dari bidang farmakologis dan laboratorium untuk meningkatkan perawatan pasien yang mengalami perdarahan. Pendekatan ini termasuk trombelastografi sebagai ukuran rinci kaskade pembekuan, asam traneksamat sebagai antifibrinolitik. Kata kunci : hipotermia, koagulopati, asidosis, perdarahan masif Damage Control Resuscitation in Intensive Care Unit Abstract Damage control resuscitation (DCR) describes an approach to the early care of very seriously injured patients. The aim is to keep the patient alive whilst avoiding interventions and situations that risk worsening their situation by driving the lethal triad of hypothermia, coagulopathy and acidosis.It is critical that the concepts and practicalities of this approach are understood by all those involved in the early management of trauma patients. Damage control resuscitation forms part of an overall approach to patient care rather than a specific intervention and has evolved from damage control surgery. It is characterised by early blood product administration, haemorrhage arrest and restoration of blood volume aiming to rapidly restore physiologic stability. The infusion of large volumes of crystalloid is no longer appropriate, instead the aim is to replace lost blood and avoid dilution and coagulopathy. In specific situations, permissive hypotension may also be of benefit, particularly in patients with severe haemorrhage from an arterial source. Damage control resuscitation has been augmented by both pharmacologic and laboratory adjuncts to improve the care of the hemorrhaging patient. These include thrombelastography as a detailed measure of the clotting cascade, tranexamic acid as an antifibrinolytic. Keywords: hypothermia, coagulopathy, acidosis, massive bleeding